Mobile Nodes as a Dynamic Management Strategy to Improve Coverage in Wireless Sensor Networks - González, Andrea Verônica; Ferreira, Paulo Roberto; Brisolara, Lisane Brisolara de (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2016)
Inspired on the force fields theory of mobile robotics, this paper defines a simple method for event-triggered wireless sensor networks reorganization through the adoption of mobile sensor nodes. Following this dynamic management strategy nodes can move itself to maximize the area coverage avoiding sense on the same place. Through experiments, this work evaluates the proposed method with different network setups, varying adopted topology (random and mesh) as well as the network density, regarding the number of events sensed by day. Furthermore, we compare the adoption of the mobility against to the load balancing state-of-the-art techniques. In random networks configurations, dynamically reorganized mobile nodes increase the coverage in low density networks, increasing the number of sensed events in around 220%. As density is increased, mobile nodes sense around 2% more events in comparison to the static ones, minimizing the coverage limitation of random deployments and approximating its efficiency to the static nodes deployed in mesh.